Evaluation of antinociceptive and analgesic properties of tramadol in cats - Basiri, Bita (2013)
The need for safe and cost effective analgesic in cats prompted investigation into the potential use of tramadol for acute pain. The hypothesis was that tramadol at a higher dose can provide a more significant analgesic effect in the post-operation period. In the first part, we assessed the thermal and mechanical thresholds following a high (4 mg/kg) and a low (2 mg/kg) dose of tramadol in comparison to acepromazine at 0.1 mg/kg, administered subcutaneously (SC) in cats without undergoing surgery. Three female and 3 male cats were utilized in a randomized cross-over manner. Thermal and mechanical thresholds were determined using two custom-made analgesiometric devices. Both thermal and mechanical thresholds were significantly higher than baseline at 3, 4, 5 and 6 hours after 4 mg/kg tramadol. Following 2 mg/kg tramadol, both thermal and mechanical thresholds were higher than baseline at 4 and 5 hours only. There were no significant changes in both thermal and mechanical thresholds at any time point after administration of 0.1 mg/kg acepromazine. The above results demonstrated that the methods of threshold measurements used in this study can differentiate if a treatment had analgesic effect. Furthermore, they showed dose-dependent response to tramadol. In the second part, we investigated the analgesic effects of 4 and 2 mg/kg of tramadol, SC, in addition to 0.1 mg/kg acepromazine as pre-medication in cats undergoing ovariohysterectomy (OHE). Following surgery, pain scores did not increase significantly from baselines in cats that received 4 mg/kg (AT4 group: 6 cats) and in 2 mg/kg (AT2 group: 6 cats) tramadol at pre-medication. Composite pain scores were lower in AT4 compared to AT2 at 4.5 and 6.5 hours after pre-medication. Pain scores increased significantly at 2.5 and 3.5 hours post-treatment in the 3 cats that received only acepromazine without tramadol (Ace group). All cats in Ace required rescue analgesia. Metatarsal pad mechanical thresholds showed a significant increase from baseline at 3.5, 4.5 and 6.5 hours post-treatment in AT4, and at 4.5 hours in AT2. Thresholds in AT4 were higher than AT2 at 4.5 and 6.5 hours. No significant change was observed in Ace. Mechanical thresholds at surgical site decreased from baselines following surgery and persisted throughout the 36 hours observation in all groups. The decrement tended to be less in AT4 compared to AT2. These results showed the requirement of an analgesic in addition to acepromazine in the pre-medication for cats undergoing OHE. In the third part, we studied the effect of tramadol at 4 mg/kg, SC, on secondary hyperalgesia. Metatarsal pad mechanical thresholds after tramadol but without undergoing surgery were compared to thresholds following tramadol and gonadectomy in six cats. There was no difference in the increment of thresholds following tramadol, with or without gonadectomy. Thresholds increased significantly from baseline between 3 to 6 hours post-tramadol, with or without gonadectomy. The results of these studies supported the use of tramadol for acute pain management in cats. Tramadol at 4 mg/kg provided more profound and longer analgesic effect than 2 mg/kg. If used at 4 mg/kg, tramadol may prevent secondary hyperalgesia for up to 6 hours after medication.